Telehealth DM Group Android Smartphones in Controlling Blood Sugar Levels in Patients with Type 2 DM - Syamsu, Muh. Nur; Sudirman, Sudirman; Ramlan, Djamaluddin (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
Diabetes mellitus (DM) is a degenerative disease with an increasing number that continues to grow from year to year. Data from the International Diabetes Federation (IDF) shows that the prevalence of diabetes patients will increase to 84%, from 82 million to 151 million. Uncontrolled blood sugar levels can cause serious diseases that affect the heart, blood vessels, eyes, kidneys, and nerves. Aim: Knowing the effectiveness of the Telehealth DM Group application in controlling blood sugar levels in DM type 2 patients. Method: This study uses Research and Development (R&D) and quasi-experimental development methods with a pre-post control group design and uses a random sampling technique. Results: The Telehealth DM Group Smartphone Android application is feasible based on expert validation tests with marks of 93.33%. There is a difference in blood sugar levels before being given pre-intervention (219 mg/dl). After being given post-intervention (160 mg /dl) with a value of 0.002, the Telehealth DM Group application can control blood sugar levels of 58.6 mg/dl with a value of 0.004. Conclusion: Telehealth DM Group Android smartphones are effective as an educational and health service media in controlling blood sugar levels in patients with type 2 diabetes mellitus.